Implementasi E-Government Melalui Magelang Smart City (Magesty) Sebagai Upaya Keberlanjutan Ekosistem UMKM Kota Magelang - Satwika, Wirati Dhira; Pujiasih, Retno; Mali, Matheus Gratiano (Journal of Public Administration and Local Governance, 2023)
Considering that MSMEs make a large contribution to the Indonesian economy, the development of information technology is increasingly being encouraged in the micro, small and medium sectors. The presence of the Magesty e-Government service is a breakthrough for the Magelang City Government in meeting the needs of its people. In the Magesty application, many MSME partners are involved, starting from food, snacks, drinks and handicrafts. This research aims to analyze the impact of implementing the Magesty (Magelang Smart City) application on the sustainability of the MSME ecosystem in Magelang City. This research method uses descriptive qualitative. The research results show that the implementation of Magelang Smart City has not had an impact on the sustainability of Magelang City MSMEs. This has not had an economic impact on MSMEs because the people of Magelang City tend not to use the Magesty platform.